ASPEK NEUROSAINS DALAM PATOFISIOLOGI PRURITUS NOKTURNAL - Reqgi First Trasia; Samsul Mustofa; Endang Purwaningsih; Sri Wahyu Herlinawati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Itching at night in scabies patients is considered a very disturbing symptom. It is known that the main role of the itch sensation and subsequent motor response is to remove environmental influences from the skin, especially arthropods. The purpose of this article is to provide an understanding of the overall physiology and associated pathophysiology of itch. This article focuses on the neuronal aspect, as the nervous system is necessary to perceive the sensation of itch, as well as the multidirectional connections between the nervous and immune systems that influence the transmission of itch from the skin to the spinal cord. Itching is felt by skin nerve fibers called pruriceptors. These primary afferent fibers function as antennae and continuously sense the skin environment to detect and respond to cues. All major afferents project to the dorsal part of the spinal cord. Peptidergic and nonpeptidergic neurons target different areas of the dorsal superficial lamina. Based on this review, it can be concluded that noxious and pruritic stimuli are mostly processed in the superficial dorsal horn, whereas deeper dorsal horn neurons receive nociceptive and pruritic input via polysynaptic innervation.